2021
DOI: 10.1038/s41392-021-00777-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 immunity and functional recovery of COVID-19 patients 1-year after infection

Abstract: The long-term immunity and functional recovery after SARS-CoV-2 infection have implications in preventive measures and patient quality of life. Here we analyzed a prospective cohort of 121 recovered COVID-19 patients from Xiangyang, China at 1-year after diagnosis. Among them, chemiluminescence immunoassay-based screening showed 99% (95% CI, 98–100%) seroprevalence 10–12 months after infection, comparing to 0.8% (95% CI, 0.7–0.9%) in the general population. Total anti-receptor-binding domain (RBD) antibodies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 50 publications
(51 reference statements)
7
41
0
Order By: Relevance
“…The meta-analyses on prevalence data showed that common residual symptoms among COVID-19 survivors at one-year post infection included fatigue/weakness (28%), dyspnoea (18%), arthromyalgia (26%), depression (23%), anxiety (22%), memory loss (19%), concentration difficulties (18%), and insomnia (12%). The qualitative review of evidence on risk factors suggested that females [20,25,32,35] and those with severe/critical COVID-19 infection [25,34,35] were at higher risk of experiencing long-term post-COVID symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The meta-analyses on prevalence data showed that common residual symptoms among COVID-19 survivors at one-year post infection included fatigue/weakness (28%), dyspnoea (18%), arthromyalgia (26%), depression (23%), anxiety (22%), memory loss (19%), concentration difficulties (18%), and insomnia (12%). The qualitative review of evidence on risk factors suggested that females [20,25,32,35] and those with severe/critical COVID-19 infection [25,34,35] were at higher risk of experiencing long-term post-COVID symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The current body of evidence suggested that female sex [20,25,32,35] and severe/critical acute infection [25,34,35] could be risk factors for experiencing long-term post-COVID symptoms. A cohort study with 342 COVID-19 patients [39] found that time to complete recovery (no ongoing symptoms) was significantly longer in those with moderate and severe/critical initial illness than mild cases, and at least one persistent symptom was reported by 16.4%, 49.5%, and 52.5% of participants in mild, moderate, and severe/critical groups at one year after infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2-specific memory T cell responses are long-lasting in recovered COVID-19 patients (37-39) even though SARS-CoV-2-specific antibody response may decrease (15,37,(40)(41)(42). Previous studies have shown that T cell responses to SARS-CoV-1 and Middle East Respiratory Syndrome Coronavirus (MERS-CoV) are long-lasting, up to >17 years (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Till January 5, 2022, there were 293.75 million confirmed cases of COVID‐19 and 5.45 million deaths 4 . There were approximately more than 200 million patients with post‐COVID‐19 condition (PCC), 5 , 6 of which over 90% suffered from persistent symptoms, including fatigue (53.1%−80%), breathlessness (43.4%−53%), anxiety (14.6%−23%), and insomnia (26%−30.8%), 7 ‐ 11 substantially reducing the quality of life 12 , 13 …”
Section: Introductionmentioning
confidence: 99%